2002
DOI: 10.1007/s00210-002-0625-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inhibitory action of ethanol on inducible nitric oxide synthesis in macrophages

Abstract: Effects of ethanol in vitro on inducible nitric oxide (NO) production in RAW 264.7 macrophages were investigated. Adding ethanol (100-600 mM) to the incubation medium simultaneously with lipopolysaccharide (LPS) concentration-dependently inhibited LPS-induced NO production without being cytotoxic. This inhibitory effect of ethanol on NO production was almost abolished when ethanol was added to the medium 12 h after the start of incubation with LPS, implying that ethanol inhibits the induction of inducible NO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…Ethanol and methanol showed harmless effects on MDA-MB-231, MCF-7 and VNBRCA1 even at the high concentration of up to 2%. Similarly, though not using the same cell lines as in our study, a previous study also found that 2.8% ethanol did not affect the cell viability of RAW 264.7 8 . In another report studying the effects of ethanol on HeLa cells, it was found that 5% ethanol (or higher concentrations) compromised cell viability 9 .…”
Section: Discussionsupporting
confidence: 42%
“…Ethanol and methanol showed harmless effects on MDA-MB-231, MCF-7 and VNBRCA1 even at the high concentration of up to 2%. Similarly, though not using the same cell lines as in our study, a previous study also found that 2.8% ethanol did not affect the cell viability of RAW 264.7 8 . In another report studying the effects of ethanol on HeLa cells, it was found that 5% ethanol (or higher concentrations) compromised cell viability 9 .…”
Section: Discussionsupporting
confidence: 42%
“…NOS inhibitor attenuated and NOS donor stimulated the apoptosis, which seems to be mediated through the generation of NO [46]. However acute EtOH inhibits the lipopolysaccharide (LPS)-induced NO response in Kupffer, hepatic endothelial cells [47], and macrophages [48,49]. Similarly acute EtOH exposure enhanced cytokine-induced iNOS expression at a pretranslational site in astroglial cells [50].…”
Section: Effect Of Etoh On Nosmentioning
confidence: 99%
“…Both acute (24 h, 150 mM) and chronic (10 days, 30 mM) EtOH exposure suppressed iNOS induction by co-administration of phorbol 12-myristate 13-acetate (PMA) and LPS in brain glial cells [46,52]. The inhibitory effects of EtOH on iNOS mRNA is not due to the metabolism of EtOH to acetaldehyde and acetate [50,53] but due to inhibiting nuclear transcription factor-kappaB (NFkappaB) [48] and inhibiting signal transducer and activator of transcription-1 (STAT-1) activation [49]. Furthermore, different doses of EtOH affected iNOS expression in glial cells.…”
Section: Effect Of Etoh On Nosmentioning
confidence: 99%
“…In inflammatory contexts, there is increase in the secretion of soluble mediators such as pro-inflammatory cytokines, including TNF-a, IL-1, IL-6 and IL-8. Activation of macrophage by pro-inflammatory cytokines is an efficient pathway to activate iNOS leading to higher synthesis of nitric oxide (NO) directly involved in macrophage bactericidal activity and efficient phagocytosis [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most reports have focussed on early alterations induced by EtOH consumption or those observed following direct in vitro addition of EtOH over macrophages and lymphocyte cultures [4][5][6][7]. The immunological alterations already reported following EtOH administration describe mainly the suppression of inflammatory-type cytokines, including reduced levels IL-2 and IFN-c [8,9], impairment of TNF-a, IL-1 and IL-6 production by human macrophages and murine Kupffer cells [10][11][12], and inhibition of iNOS induction at the transcriptional level in macrophage [3].…”
Section: Introductionmentioning
confidence: 99%